PERANCANGAN VISUAL CONTROL CHART UNTUK MENINGKATKAN EFISIENSI KINERJA KERJA DALAM PROSES PRODUKSI HARIAN PERUSAHAAN SPAREPART OTOMOTIF - Ayubi, Alif Hijau Al; Ahmad; Gozali, Lina (Universitas Tarumanagara, 2024)
Company leaders play a key role in controlling the achievement of performance indicators, especially in managing abnormal conditions in the production process. Control visualization is the main tool in supporting KPI (key performance indicator) monitoring and maintaining optimal safety, quality, productivity and delivery conditions. In the context of the manufacturing industry, as faced by the company, the complexity of production line operations is increasing. Abnormal conditions in the production line can result in decreased efficiency, waste and decreased product quality. Company leaders need to identify, analyze and overcome these abnormal conditions, where data visualization becomes a key tool in making timely decisions. Shop floor management is essential in ensuring good control of conditions on the production line. In this context, the benefits of data visualization in improving the control of abnormal conditions in industrial line processes are crucial. The Total Quality Management (TQM) approach is a strong foundation in emphasizing the importance of quality in the entire production process. TQM and shop floor management are closely related in the context of quality management and operational efficiency in the manufacturing environment. Therefore, this research aims to investigate the benefits of data visualization in improving control of abnormal conditions in industrial line processes and integrating TQM and shop floor management concepts to improve quality and operational efficiency